Analytical model for flexural damping responses of CFRP cantilever beams in the low-frequency vibration. Issue 4 (December 2018) - Yang, Mo; Hu, Yefa; Zhang, Jinguang; Ding, Guoping; Song, Chunsheng
In this paper, an analytical model for the flexural vibration damping of Carbon Fiber Reinforced Plastics (CFRP) cantilever beams was proposed, which is based on the Lamination Theory and Euler–Bernoulli Beam Theory. By using a finite element analysis and an analytical model, four sets of specific damping capacity with different pavement schemes were predicted, and flexural vibration test and damping analysis were carried out. Comparing the analytical model, finite element analysis, and test results, it could be found that the analytical model had relatively good accuracy in predicting the first-order natural frequency and specific damping capacity of the bending vibration of CFRP beams. The maximum error of the first-order natural frequency between the analysis result and the experimental result was 7.05%; the maximum specific damping capacity error was only 5.65%. Comparing the finite element analysis method and the experiment results, the maximum error of the first-order natural frequency was 7.8%, the error of the specific damping capacity was bigger, and the [±30°]5S specimen was as high as 18.7%. However, there was a significant error when the analytical model was used to predict the second-order natural frequency and the specific damping capacity of CFRP beam's flexural vibration.